2014
DOI: 10.18608/jla.2014.13.16
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Social Signal Analysis

Abstract: We present our efforts towards building an observational system for measuring classroom activity. The goal is to explore visual cues which can be acquired with a system of video cameras and automatically processed to enrich the teacher's perception of the audience. The paper will give a brief overview of our methodology, explored features, and current findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…The physiological data sources include eye-tracking, electroencephalography, facial features and arousal data (HR, blood volume pressure (BVP), electrodermal activity (EDA) and skin temperature). Various combinations of such data sources have been used in the past to explain (Raca & Dillenbourg, 2014) and/or predict (Beardsley, Hernández-Leo, & Ramirez-Melendez, 2018) learning behaviors (Furuichi & Worsley, 2018) and/or performance (Junokas, Lindgren, Kang, & Morphew, 2018).…”
Section: Motivation Of the Research And Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological data sources include eye-tracking, electroencephalography, facial features and arousal data (HR, blood volume pressure (BVP), electrodermal activity (EDA) and skin temperature). Various combinations of such data sources have been used in the past to explain (Raca & Dillenbourg, 2014) and/or predict (Beardsley, Hernández-Leo, & Ramirez-Melendez, 2018) learning behaviors (Furuichi & Worsley, 2018) and/or performance (Junokas, Lindgren, Kang, & Morphew, 2018).…”
Section: Motivation Of the Research And Research Questionmentioning
confidence: 99%
“…Results shown that low arousal was the predominant state, whereas all students were never in high arousal states in the classroom, at the same moment. In the same context, Raca and Dillenbourg (2014) used the synchronization of students' gaze direction and body postures for predicting their self-reported attention. Attention has been found to be a strong construct of engagement (Kinnealey et al, 2012;Mundy, Acra, Marshall, & Fox, 2006).…”
Section: Related Work: Utilizing Multimodal Data To Predict Learning mentioning
confidence: 99%
“…These contexts vary from games [18], [25], to assessment systems [40], to adaptive systems [32], to collaborative systems [24]. However, one common factor in these studies is the use of multiple data streams (e.g., gaze, facial expressions, Electroencephalography (EEG), heart rate, log data) to predict and explain learning performance [18], [40], behaviour [3], [42] or experience [37], [38].…”
Section: B Multi-modal Data-based Predictions In Educationmentioning
confidence: 99%
“…Additional publications relevant to the study questions we're engaged in were retrieved using Google Scholar and Google. The systematic reviews' references [17,18,23,36,[42][43][44][45][46][47][48][49][50] were also examined to ensure that no relevant papers were neglected. Only Englishlanguage articles from conference proceedings, transactions, magazines, books, essays, technical reports, white papers, and manufacturer's technical guides were studied.…”
Section: Methodsmentioning
confidence: 99%